PENGARUH WAKTU PINDAH TANAM BIBIT SAWI DAN WAKTU APLIKASI PUPUK ORGANIK TERHADAP BOBOT SEGAR SAWI (Brassica juncea L.) - Sompotan, S.; Raintung, J. S. M.; Titah, Tilda; Rantung, John L. (Universitas Sam Ratulangi, 2019)
Organic farming systems utilize organic fertilizer as the main source of nutrients for the crops. The application of organic fertilizer from animal sources, such as manure, can increase soil fertility and crop yield. This research aims to: 1) Study the effects of organic fertilizer dosage and time of application towards the fresh weight of mustard greens, and 2) determine the best application time for the maximum fresh weight of mustard greens. Factorial research with two factors was designed using a randomized block design. The first factor was dosage of organic fertilizer (A): A1 = 15 ton/ha, A2 = 20 ton/ha, A3 = 25 ton/ha, and A4 = 30 ton/ha. The second factor was the time of application (B): B1 = 10 days before planting the seeds, B2 = 15 days before planting the seeds, B3 = 20 days before planting the seeds. Every experimental unit was replicated three times, yielding 36 experimental pots. The variable observed was the fresh weight of mustard greens. Data were analyzed using ANOVA, followed by Tukey's honest significance difference test (alpha = 0.05) if significant differences were found. Results show that the interaction between dosage and time of application had significant effects on the mustard greens' leaf length, plant height, leaf count, leaf width, and fresh weight. Treatment A3B1 (25 ton/ha of organic fertilizer, applied 10 days before planting seeds) gave the heaviest weight (24,07 gram). The longer the application time, the better the effects on the plants. The application of organic fertilizer requires 10 days of incubation before the mustard greens are moved.